Short adult height increases the risk of end-stage renal disease in type 2 diabetes. Issue 9 (September 2020) - Hong, Yu Ah; Han, Kyung-Do; Yun, Jae-Seung; Sil, Eun Sil; Ko, Seung-Hyun; Chung, Sungjin
Abstract : Objective: : Although short adult height has been associated with an increasing variety of diseases and all-cause death, no reliable data exist on the association between adult height and end-stage renal disease (ESRD) in diabetic patients. We investigated the relationship between short adult height, development of ESRD, and mortality in type 2 diabetes mellitus (DM). Methods: : This nationwide population-based cohort study analyzed clinical data from a total of 2, 621, 907 subjects aged ≥30 years with type 2 DM between January 1, 2009 and December 31, 2012, using the National Health Insurance Database in Korea. Results: : During a 6.9-year follow-up period, 220, 457 subjects (8.4%) died, and 28, 704 subjects (1.1%) started dialysis. Short adult height significantly increased the incidence of ESRD and all-cause mortality in the overall cohort analysis. In multivariable Cox models, hazard ratios (HR) for the development of ESRD comparing the highest and lowest quartiles of adult height were 0.86 (95% CI 0.83–0.89). All-cause mortality also decreased with the highest height compared to patients with the lowest height, after fully adjusting for confounding variables (HR 0.79, 95% CI 0.78–0.81). Adult height had an inverse relationship to newly diagnosed ESRD (male: HR 0.86, 95% CI 0.83–0.90, female: HR 0.84, 95% CI 0.79–0.90) and all-cause mortality (male: HR 0.81, 95% CI 0.79–0.82, female: HR 0.80, 95% CI 0.78–0.82). Conclusions: : Short adult height is strongly associated with the increased risk of ESRD development and all-cause mortality in type 2 DM.